THE PHILOSOPHICAL EXAMINATION ON INTEGRATION OF KNOWLEDGE AND WAYS FORWARD - Mohd Rushdan Mohd Jailani; Nurul Ashikin Ahmat Miskam; Wan Mohd Fazrul Azdi Wan Razali; Mohd Anuar Mamat; Faszly Rahim; Mohd Azman Hashim @ Ismail; Nur Syala Abdul Latip; Nursilah Ahmad; Norazilah Noh, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
The crisis of error and confusion of knowledge in cumulative today is inevitable as it has given birth to the false leaders who are incapable of making correct decision in their scope of responsibilities. Secularism as the poisoning ideology had inflicted chaos to the proper metaphysical realm of God with the subordination of existents in ranks through their corpus of so-called modern knowledge that have been rendered dominantly yet arguably as mainstream intellectualism. The nature of unified and hierarchical knowledge is mistreated and broken into fragmentation because the supreme, first principle of Tawhid as the soul of Islamic thought is suspended in knowledge production of modern science. As an antidote to this issue fast forward after the Islamization of knowledge was introduced, the idea of integration of knowledge was also brought into the picture to resolve the same brand crisis. However, the initiative of integration of knowledge as one of those has been grappling to present its philosophical underpinnings as in tandem with Islamic worldview as the valid solution to the knowledge crisis concerned. Therefore, this conceptual paper is esteemed to examine the philosophical structure of integration of knowledge idea as seen from Islamic mega scheme of knowledge. The data collection method involved in this writing was purely library search with the selection of literature from the advocates of integration of knowledge and some referenced from Islamic epistemology. The facts gathered were analyzed through content analysis technique with the approach of philosophical argumentation. The main findings of this writing were two-folded: i) The presentation of ontological, epistemological, axiological and methodological examination of integration of knowledge idea and its limitations. ii) The proposed integration of knowledge framework as a one of the methodologies of Islamic source in knowledge production and preservation. We contend that the contribution of this writing would further reframe the implementation of integration of knowledge in academic research endeavor in the institution advocating this epistemological idea.